Assessment of Maxillary Expansion Techniques by means of 3D Elastoplastic Finite Element Static Simulation - Olesya Shosheva; Mikhail Zhmaylo; Leonid Maslov; Aleksey Borovkov; Nataliia Vishneva; Anastasiia Lanina; Andrey Yaremenko (Journal of Applied and Computational Mechanics)
Even though numerous studies considered various approaches for maxillary expansion, there is still no consensus on which method is optimal for a patient with a particular clinical picture. The purpose of this study is to determine the optimal technique from the procedures proposed by doctors for a patient with completed facial skeleton growth. In this paper we consider four scenarios of surgical intervention, i.e., without osteotomy, midpalatal suture osteotomy, experimental osteotomy of zygomatico-alveolar ridge on the both sides of maxilla, and midpalatal suture osteotomy with osteotomy of zygomatico-alveolar ridge. In addition, two experimental appliances (one-screw expander and two-screw expander) and two positioning configurations of them (parallel to the hard palate and horizontal) are under consideration at the suggestion of the doctors. The criteria for determining the optimal technique are established in the article. Three-dimensional finite element (FE) models of skull and teeth of an adult 43-year-old patient with an ossified midpalatal suture are constructed based on the results of computed tomography, while the 3D models for the expander components are built separately and combined into the full FE system. The corresponding elastoplastic properties are adopted for the bone tissues and expander components. After proper skull fixation at the bottom, a quasi-static displacement of 0.25 mm, corresponding to quarter-turn of the control screw, is applied to the expander components to stimulate the maxillary expansion. All analyses in the paper are performed in the SIMULIA Abaqus 2021 software suite. Displacements and stresses in the bone structures of the hard palate and the appliance are obtained for all the cases studied. It was revealed that the expansion of the midpalatal suture is small in the cases without surgical intervention. A significantly greater expansion of the midpalatal suture is observed as a result of midpalatal suture osteotomy. Osteotomy of the zygomatico-alveolar ridge has virtually no effect on the value of the midpalatal suture expansion. Midpalatal suture osteotomy combined with osteotomy of the zygomatico-alveolar ridge leads to maximum expansion of the midpalatal suture. However, additional osteotomy of the zygomatico-alveolar ridge induces a proportionally greater increase in the expansion value at the dental level (by 24.8–25.8%) than at the midpalatal suture level (by 10.8–16.2%). Unlike the one-screw expander, using the two-screw expander leads to a 21.4–22.9% greater expansion of the midpalatal suture in the cases with midpalatal suture osteotomy, but increases the highly stressed regions and the magnitude of plastic strains in them. The horizontal position of the expander contributes to a more symmetrical expansion of the maxilla than positioning the expander parallel to the palate. Based on the analysis performed, we believe that midpalatal suture osteotomy might be the best scenario for surgical intervention for maxillary expansion in patients with completed facial skeleton growth. The two-screw expander is more effective in terms of maxillary expansion values, but it increases the risk of bone resorption. It is also found that providing osteotomy of zygomatico-alveolar ridge and changing the position of the expander practically does not affect the expansion state. Thus, our findings can serve as a basis for doctors deciding which scenario of surgical intervention and expander configuration would be more appropriate for a particular patient.